How Does Fetal Surgery Impact Long-Term Neurological And Develop- Mental Outcomes In Children With Twin-Twin Transfusion Syndrome? - Yunike Putri Nurfauzia; I Made Adi Saputra Wijaya; Mutia Juliana; Lina Haryani (The Indonesian Journal of General Medicine, 2025)
Introduction: Twin-Twin Transfusion Syndrome (TTTS) is a serious complication in monochorionic twin pregnancies caused by unbalanced blood flow through placental vascular anastomoses. Fetoscopic laser surgery has become the primary intervention to improve survival and reduce neurological morbidity. Methods: This review synthesizes data from randomized controlled trials, prospective and retrospective cohort studies conducted over the last decade. Studies included patients undergoing fetoscopic laser surgery with follow-up periods ranging from weeks to years, assessing survival, neurological, and developmental outcomes. Results: Survival rates after fetal laser surgery range from mid-70% to mid-80%, with one trial reporting 67-68% survival without neurodevelopmental impairment at 2 years. Cerebral palsy incidence is low (1-2%), and cognitive or motor impairments occur in 2-8% of survivors. Comparisons between surgical techniques (Solomon vs. standard laser, sequential vs. selective coagulation) show similar survival and neurodevelopmental outcomes. Immediate surgery versus expectant management in early-stage TTTS showed no significant difference in 6-month survival without severe neurologic morbidity (78% vs. 77%). Laser surgery reduces severe cerebral injury compared to no treatment (5% vs. 18%). Discussion: While fetal surgery improves survival and neurological outcomes, challenges such as preterm birth and growth discordance remain. Adjunctive therapies and long-term neurodevelopmental monitoring are essential to optimize care. Conclusion: Fetoscopic laser surgery is effective in managing TTTS, offering improved survival and reduced neurological morbidity. Continued research is needed to refine techniques and adjunctive treatments